2017
DOI: 10.1038/sigtrans.2017.44
|View full text |Cite
|
Sign up to set email alerts
|

Roles of PFKFB3 in cancer

Abstract: The understanding of 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 (PFK-2/FBPase 3, PFKFB3) has advanced considerably since its initial identification in human macrophages in the mid-1990s. As a vital regulator of glycolysis, accumulating studies have suggested that PFKFB3 is associated with many aspects of cancer, including carcinogenesis, cancer cell proliferation, vessel aggressiveness, drug resistance and tumor microenvironment. In this review, we summarize current knowledge of PFKFB3 regulation by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
210
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(214 citation statements)
references
References 131 publications
3
210
0
1
Order By: Relevance
“…It was hypothesised that replacement of the pyrimidine core with aromatic bicycles containing heteroatoms judiciously positioned would offer increased opportunities of hydrogen bondingw ith the sidec hains of residues ASN163a nd SER152, as well as potential p-sulfurbonding [51,52] with the CYS154 residue and increased binding-site occupancy.D ocking studies suggested that a6 -aminoquinoxaline core would be able to satisfy the envisioned interactions (see Figure 3f or the proposed binding mode of model compound 19). A1 808 flip of the ASN163 carboxamide group, compared with the X-ray structure reported (PDB ID:2 I1V), would occur with 39 %p robability,a ccording to the Lovell,W ord andR ichardson rotamer library.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…It was hypothesised that replacement of the pyrimidine core with aromatic bicycles containing heteroatoms judiciously positioned would offer increased opportunities of hydrogen bondingw ith the sidec hains of residues ASN163a nd SER152, as well as potential p-sulfurbonding [51,52] with the CYS154 residue and increased binding-site occupancy.D ocking studies suggested that a6 -aminoquinoxaline core would be able to satisfy the envisioned interactions (see Figure 3f or the proposed binding mode of model compound 19). A1 808 flip of the ASN163 carboxamide group, compared with the X-ray structure reported (PDB ID:2 I1V), would occur with 39 %p robability,a ccording to the Lovell,W ord andR ichardson rotamer library.…”
Section: Resultsmentioning
confidence: 91%
“…[17] PFKFB3 is thus unsurprisingly overexpressed in many cancert ypes, including colon,p rostate, pancreatic, breast, thyroid, lung and ovarian tumours, as well as in leukaemia, for which it maintains high levels of F-2,6-BP, promoting glycolysis. [18,19] As such, PFKFB3i s believed to be ap romising target fort he inhibition of glycolysis and forc ancer therapy. [19][20][21] Additional recent results also suggest adetermining role for PFKFB3 in regulating autophagy in rheumatoid arthritis Tc ells, [22] and in promoting cell cycle progression througha ctivation of the cyclin-dependent kinases CDK1 [23] and CDK4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Among all PFKFBs, PFKFB3 exerts a central role in controlling glycolysis flux and has aroused a great deal of attention in recent years. 34 In addition to activation of mTORC1, inactivated mutation of Pten or the aberrant activation of Ras and PI3K have been shown that take part in the regulation of glycolysis and tumorigenesis through modification of PFKFB3 expression. 35,36 However, the detailed transcriptional regulation mechanisms of PFKFB3 expression are far from fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…29 In recent studies, blockage of PFKFB3 suppressed the growth of various cancer cells, such as head and neck squamous cell carcinoma cells 17 and breast cancer cells. 29 In recent studies, blockage of PFKFB3 suppressed the growth of various cancer cells, such as head and neck squamous cell carcinoma cells 17 and breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%